Analysis of Trade Distribution Network Structure on Livestock Commodities among Regions in Indonesia - Andi Ishak; Emlan Fauzi; Erpan Ramon; Jhon Firison; Zul Efendi; Harwi Kusnadi (Perum BULOG, 2022)
The inter-regional trade distribution networks are essential for constructing a more efficient trade distribution system. This study aimed to compare the structure and role of regions in the distribution network of trade in beef, broiler meat, and broiler eggs in Indonesia. Secondary data analysis was carried out on the distribution network between regions of each commodity published by BPS-Statistics Indonesia in 2019 using UCINET 6 Software. The results showed that the structure of the beef trading networks in Indonesiaconsisted of one component, while chicken meat and eggs, respectively, consisted of four and two elements. East Nusa Tenggara Province was isolated from two of the three distribution networks: beef and egg trade. The structure of the three trade distribution networks was relatively the same in the variables of network density (between 5.9–7.2 percent), number of clicks (20–21 clicks), reciprocity (14.1–15.7 percent), degree of centralization (31.4–34.1 percent), mean distance (2.331–2.664 steps), and network diameter (6–7).The distribution network of trade of essential livestock commodities in Indonesia is still concentrated in Java, especially DKI Jakarta for beef and East Java for broiler meat and eggs.